Nutrient composition and starch characteristics of Quercus glandulifera Bl. seeds from China. (15th October 2015) - Li, Songnan; Zhou, Yibin; Liu, Mei; Zhang, Yang; Cao, Shengnan
Highlights: The nutritional composition of Quercus glandulifera Bl. seeds was studied. The SFA:MUFA:PUFA ratio of Quercus glandulifera Bl. oils was close to 1. Quercus glandulifera Bl. seeds had high contents of vitamins A and E. Quercus glandulifera Bl. starch characteristics were studied. Abstract: The chemical composition and starch characteristics of acorn ( Quercus glandulifera Bl. ) were studied. The moisture content of acorn seeds was 7.55%. The crude fat, crude protein, dietary fiber, total ash, and nitrogen-free extract contents of acorn seed were 4.20%, 10.16%, 2.95%, 0.03%, and 82.66%, respectively, on a dry weight basis. Linoleic, oleic, and palmitic were the most predominant fatty acids. UFA:SFA and SFA:MUFA:PUFA ratios were 2.6:1 and 1.25:1.34:1, respectively. The essential amino acid content from acorn seeds was low based on FAO reference values. Acorn seeds were a good source of Fe, Zn, and Mn. The contents of vitamins A and E were 1.40 mg RE/100 g and 10.78 mg/100 g, respectively. Starch extracted from acorn seeds had round, triangle, and elliptical morphology with granule size of 3.3–126.2 μm. The ratio between amylose and amylopectin contents was 25.39:72.94. Acorn starch had a typical A-type crystal pattern with 23.53% relative crystallinity. The gelatinization temperature was 66.53 °C and the transition enthalpy was 4.33 J/g.